2017
DOI: 10.13040/ijpsr.0975-8232.8(6).2712-19
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: The objective of this study was to assess drug therapy problems (DTPs) and their predictors among hypertensive patients on follow up at Dil-Chora Referral Hospital, Ethiopia. Methods: Hospital based cross-sectional study involving medical record review was conducted from February-to-April 2015 using a structured questionnaire and this was complemented by a face-to-face interview. Adult hypertensive patients aged ≥18 years who were on follow-up for at least 3-months were enrolled in the study using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
1
1
Order By: Relevance
“…Potential adverse drug reaction event in the combination of medications treatment higher than single medication treatment. This study contrasting to another study who reported the most common drug therapy problems was the need for additional drug therapy (Yimama et al, 2018;Argaw et al, 2019;Hussen et al, 2017). Percentage of DTP events in this study is visualized in Figure 1.…”
Section: Drug Therapy Problemscontrasting
confidence: 86%
See 1 more Smart Citation
“…Potential adverse drug reaction event in the combination of medications treatment higher than single medication treatment. This study contrasting to another study who reported the most common drug therapy problems was the need for additional drug therapy (Yimama et al, 2018;Argaw et al, 2019;Hussen et al, 2017). Percentage of DTP events in this study is visualized in Figure 1.…”
Section: Drug Therapy Problemscontrasting
confidence: 86%
“…Several studies in some countries such as Malaysia, Ethiopia, and Nigeria about DTPs in T2DM with hypertension have shown that each diabetes patients experienced at least one of drug therapy problems (Huri & Wee, 2013;Yimama et al, 2018;Argaw et al, 2019;Hussen & Daba, 2017;Ayele et al, 2018;Ogbonna et al, 2014). Drug therapy problems may lead to elevating morbidity, disability, mortality, health care cost, low adherence, and prolonged hospitalization (Nivya et al, 2015;Claydon-Platt et al, 2012).…”
Section: Introductionmentioning
confidence: 99%